2011
DOI: 10.1007/s10519-011-9492-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Factors Influencing BMI Development from Adolescence to Young Adulthood

Abstract: BMI increases progressively from adolescence to young adulthood. The aims of the present study were firstly, to investigate the extent to which genetic and environmental influences account for differences in BMI trajectories during this period, and secondly to examine whether boys and girls show divergences in these influences, as their BMI normally start differing across adolescence. The study sample consisted of 4,915 monozygotic and like- and unlike-sex dizygotic twins, born between 1975 and 1979. Data on B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 54 publications
(55 reference statements)
3
16
0
Order By: Relevance
“…Nevertheless, one of the major issues posing potential challenge is that many twin data sets contain individuals across a wide range of age and the variances of genetic and environmental components for many complex traits such as body mass index (BMI) and height change over age (Lajunen et al 2009;Elks et al 2012) or birth cohorts (Silventoinen et al 2000). For example, the variances of genetic and environmental components and thus the heritability of BMI have been found to diverge with age in a Finnish study of adolescent twins (Lajunen et al 2009) and another of adolescents and young adults (Ortega-Alonso et al 2012), implying that potential gene-environment (G 3 E) interactions play a notable role in these complex traits. During childhood when a twin pair is raised in a similar environment, the common environmental effects may be present in early childhood when children are dependent on their parents and then drop after midchildhood when they start to get more independence (Silventoinen et al 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, one of the major issues posing potential challenge is that many twin data sets contain individuals across a wide range of age and the variances of genetic and environmental components for many complex traits such as body mass index (BMI) and height change over age (Lajunen et al 2009;Elks et al 2012) or birth cohorts (Silventoinen et al 2000). For example, the variances of genetic and environmental components and thus the heritability of BMI have been found to diverge with age in a Finnish study of adolescent twins (Lajunen et al 2009) and another of adolescents and young adults (Ortega-Alonso et al 2012), implying that potential gene-environment (G 3 E) interactions play a notable role in these complex traits. During childhood when a twin pair is raised in a similar environment, the common environmental effects may be present in early childhood when children are dependent on their parents and then drop after midchildhood when they start to get more independence (Silventoinen et al 2009).…”
mentioning
confidence: 99%
“…For example, the variances of genetic and environmental components and thus the heritability of BMI have been found to diverge with age in a Finnish study of adolescent twins (Lajunen et al 2009) and another of adolescents and young adults (Ortega-Alonso et al 2012), implying that potential gene-environment (G 3 E) interactions play a notable role in these complex traits. During childhood when a twin pair is raised in a similar environment, the common environmental effects may be present in early childhood when children are dependent on their parents and then drop after midchildhood when they start to get more independence (Silventoinen et al 2009).…”
mentioning
confidence: 99%
“…BMI increases progressively from adolescence to young adulthood. It has been found that adolescent BMI is highly heritable (70–90%) [14]. The BMI transition from adolescence to young adulthood was best described by a quadratic trajectory that was highly accounted (61.7–86.5%) by additive genetic influences [14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that adolescent BMI is highly heritable (70–90%) [14]. The BMI transition from adolescence to young adulthood was best described by a quadratic trajectory that was highly accounted (61.7–86.5%) by additive genetic influences [14]. Additionally, twin studies have shown that breast size is about 56% heritable [15].…”
Section: Introductionmentioning
confidence: 99%
“…15 In addition, other familial factors, such as learned eating habits, likely also contribute to an individual’s weight. Dietary behaviors learned as a child generally continue on into adulthood.…”
mentioning
confidence: 99%